Answer:
Option A. f(x) = 4x + 7
Step-by-step explanation:
To obtain the answer to the question, we simply try each of the equation using the first two value of x in the table to see which of them will satisfy the table. This is illustrated below:
For option A
1. f(x) = 4x + 7
x = - 1
f(x) = 4(-1) + 7
f(x) = - 4 + 7
f(x) = 3
2. f(x) = 4x + 7
x = 0
f(x) = 4(0) + 7
f(x) = 0 + 7
f(x) = 0
For option B
1. f(x) = 7x - 4
x = - 1
f(x) = 7(-1) - 4
f(x) = - 7 - 4
f(x) = - 11
2. f(x) = 7x - 4
x = 0
f(x) = 7(0) - 4
f(x) = 0 - 4
f(x) = - 4
For Option C
1. f(x) = -4x - 1
x = - 1
f(x) = -4(-1) - 1
f(x) = 4 - 1
f(x) = 3
2. f(x) = -4x - 1
x = 0
f(x) = -4(0) - 1
f(x) = 0 - 1
f(x) = - 1
For Option D
1. f(x) = x + 7
x = - 1
f(x) = - 1 + 7
f(x) = 6
2. f(x) = x + 7
x = 0
f(x) = 0 + 7
f(x) = 7
From the illustrations made above, only option A satisfy the table.